Formation of Students' Character and Abilities Through the Integration of Education and Management - Siagian, Ester Mawar; C. Tampubolon, Tanggapan; Handayani, Rina; Simangunsong, Herlina; Gaol, Dinata Lumban (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
This research discusses the formation of students' character and abilities through the integration of education and management. The main focus of this research is to explore how effective education management can integrate relevant curricula with students' character values and competencies. Through the integration-interconnection approach in curriculum policy, this study shows that education not only includes the mastery of knowledge, but also the development of balanced attitudes and skills. By implementing school-based management, schools can create synergies between curriculum development and learning practices that support the formation of students' character. This study uses a qualitative method with data analysis based on interviews, observations, and documentation to gain an in-depth understanding of the application of integration management in the context of education. The results show that collaboration between teachers, students, and parents is essential to achieve holistic educational goals, as well as produce students who are not only academically intelligent but also have strong character.